Pengaplikasian Prosedur Perhitungan untuk Menentukan Produksi Batik Tulis Madura Menggunakan Metode Fuzzy Database Model Tahani - Miskaram, Muh Syarifuddin Syafiqy; Alisah, Evawati; Nasichuddin, Achmad (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
One of the subdivisions of fuzzy logic is the study of the fuzzy database with Tahani model which is described as a model used to process data searches based on operations in fuzzy set theory to obtain appropriate information so that the data search process becomes accurate. The research aims to implement the Fuzzy Database with Tahani Model in determining the appropriate variant of batik tulis with the specified criteria. The initial step of the research is fuzzification, namely determining the domain of each complete variables with intervals of numerical variables and linguistic variables. In this research some variables were used: the price of the cloth, the number of colors and the work durations. Each variable is divided based on the interval between the lowest data and the highest data so that the variable price of the cloth is divided into 4, the number of colors is 3, and the work durations is 5. Then determine the membership function, the variable price of cloth, the number of colors, and the work duration using a linear model and triangle in determining the degree of its membership. Data tabulation from strict sets to fuzzy sets with numerical variables and linguistic variables. In preparing the criteria, 60 rule bases are based on the theory of consumer needs for batik tulis. Not all rule bases occur, because the data collects only a few criteria. Determining the value of fire strength, using the AND rule means selecting the minimum degree of membership from the available. The recommendation results determine to sort the washing machine data that has the highest fire strength value to the smallest fire strength value from each criterion.